Diversity, difference and belonging in childhood: Issues for foster care and identities - Ann Phoenix (Social Work and Society)
Since the 1970s, those who support and those who oppose 'transracial' fostering and adoption have often been deeply divided. In transracial placements, diversity, difference and belonging are at the heart of developments in foster care and adoption. Yet, relatively little is currently known about how these issues impact on family practices and experiences. This paper aims to contribute to understanding of these issues by considering background issues necessary to informing policies and practices in foster care. It draws on the retrospective narratives of adults who grew up in visibly ethnically different households.